A Corpus Based Analysis of Explicitation and Neutralization Strategies in ECOWAS French Translations of Nigerian Political Discourse (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
This paper investigates the translation strategies employed in rendering Nigerian political discourse into French for dissemination within the Economic Community of West African States. Using a corpus based approach, the study examines a specialized collection of ECOWAS official documents, policy briefs, and communiqués translated from English Nigerian political texts into French between 2015 and 2023. The analysis focuses on two principal translation strategies: explicitation, whereby implicit information in the source text is made explicit in the target text, and neutralization, whereby culturally specific or politically charged terminology is rendered more neutral or generic. The findings reveal systematic patterns in how Nigerian political concepts, particularly those rooted in local idioms, proverbial expressions, and culturally specific institutions, are transformed in translation. Explicitation strategies are frequently employed to clarify opaque cultural references for a diverse West African francophone audience, while neutralization strategies are deployed to manage politically sensitive content and to conform to the diplomatic register of ECOWAS discourse. The study contributes to the growing field of African translation studies and offers insights into the linguistic mediation of political communication in multilingual regional organizations.